Oral Glucose Tolerance is Associated with Neuroelectric Indices of Attention Among Adults with Overweight and Obesity. Issue 10 (11th September 2018) - Niemiro, Grace M.; Skinner, Sarah K.; Walk, Anne M.; Edwards, Caitlyn G.; De Lisio, Michael; Holscher, Hannah D.; Burd, Nicholas A.; Khan, Naiman A.
Abstract : Objective: This study aimed to elucidate the relationship between glucose levels and insulin resistance and sensitivity obtained from oral glucose tolerance tests and neurophysiological indices of attention among adults with overweight and obesity. Methods: Forty adults with overweight or obesity (BMI ≥ 25 kg/m 2 ) underwent dual‐energy x‐ray absorptiometry to assess visceral adipose tissue. Repeated venous blood samples were collected during an oral glucose tolerance test to measure insulin resistance (homeostatic model assessment of insulin resistance) and indices of insulin sensitivity (Matsuda index and Stumvoll metabolic clearance rate). Attention was assessed using event‐related brain potentials recorded during a visual oddball task. Amplitude and latency of the P3 wave form in a central‐parietal region of interest were used to index attentional resource allocation and information processing speed. Results: Following adjustment for visceral adipose tissue, reduced values of Matsuda index and Stumvoll metabolic clearance rate (indicating poor insulin sensitivity) were correlated with longer peak latency, whereas insulin area under the curve was positively related to peak latency, indicating slower information processing. Individuals with decreased insulin sensitivity (Matsuda index < 4.3) had significantly longer P3 latencies compared with individuals with normal insulin sensitivity. Conclusions: Higher fasting glucose, but not homeostatic model assessment of insulin resistance, and reduced indices of glucose sensivity are associated with decrements in attention characterized by slower reaction time and slower information processing speed among adults with overweight and obesity.